Finite element analysis on the thermo-convective non-isothermal nanofluid flow in MHD Hall generator system with Soret and Dufour effects. (November 2022) - Ali, Liaqat; Ali, Bagh; Habib, Danial; Al Mdallal, Qasem
Abstract: Theoretical work for Cattaneo–Christov impacts on the non-isothermal flow of micropolar nanofluids with the application of a Hall magnetohydrodynamic (MHD) generator across a non-linearly enlarging sheet is discussed in this study. Fluid flow focuses on the impacts of Joule and viscous dispersion. A substantial electromagnetic field is utilized orthogonally to the fluid flow. The physical and geometric aspects of the study are capable of generating some findings of practical importance for thermally efficient devices. The momenta (for bulk flow and micromotion), heat transport, and concentration phenomena are formulated in the form of partial differential equations (PDEs) with the determination of conditions on the bounding wall of the sheet. The set of partial differential equations is transmuted with the help of similarity vectors. Then the finite element method (FEM) yields a viable solution. The validation of the FEM code in the Matlab script is assured when compared with the previous findings for some particular cases. The effects of various parameters on the varying characteristics of primary and secondary flow velocities, micro-motion, temperature, and nanoparticle concentration are observed, including the Hall current parameter (n), the micropolar parameter (G), the magnetic parameter (M), the thermophoretic parameter (Nt), the Cattaneo–Christov thermal relaxation parameter ( γ T ), the Brownian motion parameter (Nb), and the non-linear wall stretching factor (m) is observed. The progressing inputs of (M) impeded the primary flow and micromotion, but it enhanced the secondary flow and temperature. It is observed that the temperature and velocity profiles are reduced while microrotation and secondary flow velocity are intensified with an increasing variety of the Hall current parameter. The findings are tabulated and graphed in detail.